Analisis Value For Money Dalam Menilai Kinerja Keuangan Pemerintah Desa (Studi Kasus Pada Desa Ribang Kecamatan Koting Kabupaten Sikka) - Kandida Agatha Dua (Student Scientific Creativity Journal, 2023)
This study aims to determine whether the financial performance of the government of Ribang Village, Koting District, is economical, efficient and effective based on the concept of value for money. This study used a quantitative approach originating from the office of Ribang Village, Koting District. Analyzed using Microsoft Excel and value for money formula. The results of the research conducted concluded that the financial performance of Ribang Village, Koting District, from an economic perspective, in 2018 was quite economical and in 2019-2021 it was economical. efficiency category, (2) whereas in 2020 the index was not efficient, (3) the financial performance of Ribang Village, Koting District in terms of effectiveness in 2018-2021 was quite effective.